A Robust Incremental Power Grid Analyzer by Macromodeling Approach and Orthogonal Matching Pursuit - Lee, Yi-Hsuan; Lee, Yu-Min; Cheng, Liang-Chia; Chang, Yen-Tang (My University, 2012)
As VLSI techniques are getting more and more advanced, the size of the power grid network increases dramatically. Therefore, the power grid analysis becomes a challenging task during the design procedure. This work utilizes the macromodeling technique [1] and enhances the Orthogonal Matching Pursuit (OMP) based method [2] to develop an effective and robust incremental analysis method for the power grid network, MA-OMPt. Given a power grid network, MA-OMPt not only can deal with the change of its element values but also can handle the modification of its topology. The experimental results show that MA-OMPt can be an order of magnitude faster than the OMP-based method [2] which can only deal with the change of element values of the power grid. The experimental results also demonstrate that MA-OMpt can accurately and efficiently handle the modified topology of the power grid network.